Accuracy of intra-operative frozen section consultation in south of Iran during four years - Geramizadeh Bita; Larijani Taghi; Owji Seyed-Mohammad; Attaran Seyed; Torabinejad Simin; Aslani Fatemeh; Monabati Ahmad; Kumar Perikala; Tabei Seyed-Zeyaedin (Wolters Kluwer Medknow Publications, 2010)
Background: Accuracy of intraoperative frozen section diagnosis is an important part of quality control in surgical pathology. In this study we try to evaluate the frozen section diagnosis in our center, a referral center in southern Iran. Materials and Methods: During the four-year-period of study, all the frozen sections in the affiliated hospitals of Shiraz University of Medical Sciences were evaluated. Discrepant cases were studied to find out reasons for their inaccuracies. Results: In the four years, 759 frozen sections have been done, 25 of which showed discordant results. The most common site of frozen section and discrepancy was in central nervous system tumors. The reason for inaccuracy in frozen section diagnosis in 52% of cases was proved to be interpretative, 44% sampling error and the remainder due to lack of clinical information of the pathologist. Conclusion: Accuracy of our intraoperative consultation is comparable with other centers in Western countries. Most of the discrepancies can be prevented by providing more clinical information for the pathologist and more accurate sampling.